Diagnostic Accuracy in Fit-for-Purpose PD-L1 Testing. Issue 4 (April 2019) - Cheung, Carol C.; Lim, Hyun J.; Garratt, John; Won, Jennifer; Gilks, C. Blake; Torlakovic, Emina E.
Abstract : PD-L1 testing by immunohistochemistry (IHC) has presented significant challenges not only for clinical laboratories, but also for external quality assurance (EQA) entities that provide proficiency testing (PT) for clinical laboratories. Canadian Immunohistochemistry Quality Control (CIQC) has used educational runs to explore approaches to sample design and analysis of results that would enhance patient safety. As PT for predictive biomarkers requires modeling at every level (design of the run, assessment of the run, and reporting of "pass" or "fail") based on "fit-for-purpose" principles, CIQC has applied those principles to PD-L1 PT runs. Each laboratory received unstained slides with TMA tissue cores from 104 randomly selected primary NSCLC and tonsil tissues to test with their current PD-L1 assay. Diagnostic sensitivity and specificity were calculated against designated gold standards based on the "3D" approach (drug-disease-diagnostic assay). Depending on the selection of fit-for-purpose gold standards and also on the selection of what was considered fit-for-purpose cut-off points, great variation in the performance (accuracy) of both companion/complementary diagnostic assays and laboratory developed tests was seen. "Fit-for-purpose" in PT for PD-L1 testing entails that the purpose(s) of each PT run is declared a priori, that the PT program has selected/designated purpose-specific gold standard results for the PT challenge, and that the PT materials for the PT run are designed and constructed to enable calculations of diagnostic accuracy.